2022
DOI: 10.1097/mop.0000000000001215
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of intrinsic acute kidney injury

Abstract: Purpose of reviewThis review focuses on the pathogenesis of intrinsic acute kidney injury (AKI), emphasizing recent advances that hold therapeutic promise.Recent findingsEnhanced endothelin and reduced endothelium-derived nitric oxide release in AKI can be blocked using endothelin receptor antagonists or nitric oxide supplementation. Vasodilatory agents such as theophylline and caffeine may prevent AKI. Free labile iron is a potent factor in the generation of reactive oxygen species and tubule damage in AKI. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Statins directly act on endothelial cells by enhancing their ability to generate nitric oxide (NO) and upregulate nitric oxide synthase (eNOS) (Laufs et al, 1997;Kureishi et al, 2000). Research has reported that the use of endothelin receptor antagonists or supplementation with NO can block the enhancement of endothelin and the reduction of endothelial-derived NO release in AKI (Devarajan, 2023). The role of preoperative statin treatment was controversial in reducing the incidence of CKA-AKI or mortality (Argalious et al, 2010;Park et al, 2016;Zheng et al, 2016).…”
Section: Figurementioning
confidence: 99%
“…Statins directly act on endothelial cells by enhancing their ability to generate nitric oxide (NO) and upregulate nitric oxide synthase (eNOS) (Laufs et al, 1997;Kureishi et al, 2000). Research has reported that the use of endothelin receptor antagonists or supplementation with NO can block the enhancement of endothelin and the reduction of endothelial-derived NO release in AKI (Devarajan, 2023). The role of preoperative statin treatment was controversial in reducing the incidence of CKA-AKI or mortality (Argalious et al, 2010;Park et al, 2016;Zheng et al, 2016).…”
Section: Figurementioning
confidence: 99%